The Collaboration of Herbart Method with Cooperative Learning: Optimizing Writing Skills at IAIN Madura - Nurlaila; Muassomah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study aims to reveal the optimization of students' Arabic writing skills through the collaboration of Herbart method with cooperative learning. Using a qualitative method, the study informs that the implementation of Herbart method in the basic concepts of writing and the writing of hamzah is carried out in five stages, i.e. planning, material presentation, material association, conclusion, and application. In this case, the cooperative learning is placed in the fifth stage, i.e. application, by providing in-group exercises to students. With this collaboration, the students are able to make Arabic sentences based on the elements of writing that have been studied, such as making sentences from words starting with hamzah, analyzing a word form and converting it into another form, and being able to write words and their harakat correctly. Thus, this study concluded that the collaboration of Herbart method with cooperative learning was able to improve students' Arabic writing skills by applying several exercises in groups; it makes students accustomed to writing in Arabic.